2005
DOI: 10.1177/0143831x05049404
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity and Health-Related Outcomes among Different Types of Temporary Workers

Abstract: Over the past few decades, the number of flexible workers has increased, a situation that has captured researchers’ attention. Traditionally, temporary workers were portrayed as being disadvantaged compared to permanent workers. But in the new era, temporary workers cannot be treated as a homogeneous group. This study distinguishes between four types of temporaries based on their contract preference and employability level. Furthermore, it compares them with a permanent group. Whether these groups differ on jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 31 publications
5
113
0
12
Order By: Relevance
“…working populationbased versus age-or sex-specific groups), or the variety of health outcomes examined [Aronsson et al, 2002;Saloniemi et al, 2004;Silla et al, 2005]. Cultural, regulatory, labour market and social welfare regime distinctions between countries also play a role in shaping precarious-employment-health relationships [Virtanen et al, 2005;Kalleberg, 2009;Kim et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…working populationbased versus age-or sex-specific groups), or the variety of health outcomes examined [Aronsson et al, 2002;Saloniemi et al, 2004;Silla et al, 2005]. Cultural, regulatory, labour market and social welfare regime distinctions between countries also play a role in shaping precarious-employment-health relationships [Virtanen et al, 2005;Kalleberg, 2009;Kim et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all of the participants reported themselves as involuntary employees. In a study that investigated job insecurity and health-related outcomes among different types of temporary workers Silla et al [9] found that traditional temporary workers had lower life satisfaction than transitional, permanent temporaries and permanents. They argued that traditional temporaries perceived themselves as having less control over their environment.…”
Section: Discussionmentioning
confidence: 99%
“…The core of employees with a relatively secure labour market status is usually surrounded by spheres and sectors of a "buffer workforce" with various forms of more unstable and insecure work arrangements that carry higher risks of unemployment and other social disadvantages [8][9][10][11][12][13][14]. The relationship between different types of insecure employment and health outcomes continues to be a subject of much debate, with some researchers suggesting that it can be beneficial to workers from the perspective of allowing them to control their work time, sample a variety of work experiences, prepare for permanent employment, and positively combine work and family life, particularly for women [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In general, employees tend to have a strong preference for permanent employment (Silla, Gracia and Peiro, 2005). According to Marler and Milkovich (2000), this is partly because employees believe that permanent jobs yield greater returns.…”
Section: The Employee Dilemma: Equal Work and Equal Pay Versus Steppimentioning
confidence: 99%